Malaysian Journal of Medical Sciences’ Performance Status in 2018 - Zulkapli, Nour Azimah (Malays J Med Sci, 2019)
The Malaysian Journal of Medical Sciences (MJMS) would like to present a brief report of its progress in 2018 with a purpose to provide a clear picture of how it has performed so far. This report may considered as a helpful information, especially, to future authors who wish to submit their articles to MJMS. This report summarised the information of the total of original manuscripts received based on manuscript type, authors’ country of origin and total of original manuscripts received by month. It also reveals the statistics of the final decisions made based on manuscript type, the accept-reject ratio by the editor and the time taken from submission to decision for all manuscripts submitted throughout 2018.